Wiley CMA exam review study guide 2023. - Budd, Cassy; Holderness, Kip; Olsen, Kari; Swain, Monte R.; Yuschak, Marjorie; Phelan, Tamara (John Wiley & Sons, Inc., 2023)
"The Wiley CMA Exam Review 2023 Part 1 Study Guide: Financial Planning, Performance, and Analytics Set (1-year access) is a comprehensive and accurate handbook designed to help you identify and master each of the competencies covered by the first part of the 2023 Certified Management Accountant exam. This essential package also includes a full year of access to the Wiley online test bank, which offers over 2100 practice questions covering every aspect of Part 1 of the Certified Management Accountants exam. You'll also find 21 sample essays, as well as comprehensive answer explanations."--Amazon.com.